Extending the Minimum Information About BIobank Data Sharing Terminology to Describe Samples, Sample Donors, and Events - Eklund, Niina; Andrianarisoa, Ny Haingo; Van Enckevort, Esther; Anton, Gabriele; Debucquoy, Annelies; Mueller, Heimo; Zaharenko, Linda; Engels, Caecilia; Ebert, Lars; Neumann, Michael; Geeraert, Joachim; T'Joen, Veronique; et al. (Biopreservation and biobanking, 2020)
Introduction: The Minimum Information About BIobank data Sharing (MIABIS) was initiated in 2012. MIABIS aims to create a common biobank terminology to facilitate data sharing in biobanks and sample collections. The MIABIS Core terminology consists of three components describing biobanks, sample collections, and studies, in which information on samples and sample donors is provided at aggregated form. However, there is also a need to describe samples and sample donors at an individual level to allow more elaborate queries on available biobank samples and data. Therefore the MIABIS terminology has now been extended with components describing samples and sample donors at an individual level.
CRIS-Team WoS Importer:2020-05-02